DESIGN OF INTERACTIVE LEARNING MEDIA BASED ON AUGMENTED REALITY TECHNOLOGY IN THE SUBJECT BASICS OF ELECTRONIC ENGINEERING AT SMK NEGERI 1 BUKITTINGGI - Marina Putri, Clariza; Hidayat, Hendra (PT Wahana Global Education, 2025)
Basic electronics learning in Vocational High Schools (SMK) often faces challenges in delivering complex and abstract material. Conventional learning methods that rely on textbooks and two-dimensional diagrams are less effective in improving student understanding. To overcome this problem, this research aims to design interactive learning media based on Augmented Reality (AR) technology in Basic Electronics Engineering subjects at SMK Negeri 1 Bukittinggi. The development of this learning media uses the Multimedia Development Life Cycle (MDLC) method which consists of six stages: conceptualisation, design, material collection, assembly, testing, and distribution. The resulting media allows students to interact with electronic objects in three-dimensional form and provides interactive simulations that enhance the learning experience. The results of validation by media experts showed a feasibility level of 97.5%, while validation by material experts scored 93%, both in the ‘Very Feasible’ category. Thus, this AR-based learning media can be an innovative solution to improve students' understanding in learning basic electronics and support their readiness to face the challenges of the Industry 4.0 era.